Boosting NOMA systems through smart metasurfaces - Di Marco, Piergiuseppe; Valentini , Roberto; Santucci , Fortunato; Pettanice, Giuseppe; Antonini, Giulio (Frontiers in Communications and Networks, 2022)
Smart metasurfaces have recently emerged as a promising paradigm for next-generation wireless communication systems, providing a reconfigurable radio propagation environment for a wide range of services and applications. In this paper, we discuss how to include and exploit smart metasurfaces into a 6G environment employing non-orthogonal multiple access (NOMA) communications. We identify the key challenges in the characterization of NOMA systems assisted by metasurfaces, which encompass the mutual coupling between electromagnetic fields in the scattering surfaces and its impact on the signal-to-interference-plus-noise ratio at the receiver. Furthermore, we describe opportunities and limitations for fully integrated systems.